The Effect of Social Media on Public Opinion in the 2024 Medan Regional Election Campaign Based on the Perception of PPKN E 2021 Students - Samura, Laras Hilda; Rusnita, Ayu Novidaniati; Zahra, Muthia Ivana; Sembiring, Julianti; Halking, Halking (Education Achievement: Journal of Science and Research, 2024)
This study aims to examine the influence of social media on public opinion of PPKn E 2021 students in the 2024 Medan Pilkada campaign. Social media, as a dominant communication platform in the digital era, has a significant role in shaping public perception and opinion. This study uses a qualitative descriptive method with a phenomenological approach. Data were collected through in-depth interviews with 10 PPKn E 2021 students who actively use social media. The results of the study indicate that social media is the main source of political information for students, but also has the potential to cause information bias. Social media content, such as campaign videos and posts about visions and missions, influences students’ perceptions of candidates. Social media also facilitates political participation, but is susceptible to manipulation and polarization due to the influence of hoaxes and black campaigns. Political campaign strategies on social media can increase or decrease students’ trust in the democratic process. This study highlights the importance of digital literacy and ethical and professional use of social media in political campaigns.